Software livre e educação: políticas públicas de incentivo ao uso de software livre em escolas de ensino básico em Minas Gerais - Nilson Ferreira Rocha (2018)
The use of Free Software is increasingly present in young people's lives. Today the vast majority of smartphones run the Android operating system, which is a derivative of Free Software, because we believe in the sharing of ideas and collective intelligence, that education is a way to construct critical subjects of their reality and that technology is a possible path in the transformation of these subjects. The present work aims to find information about the investments of the state government of Minas Gerais for the use of free software in public elementary schools from 2011 to 2017. Due to a large number of computer labs present in schools and the constant complaint of teachers about software and equipment, the text tries to understand the investments in teacher training for the use of free software and public policies and government programs to promote the use of tools available in school. For that, we performed a quantitative and qualitative analysis of the data, with information based on data from the Minas Gerais government and also based on data from research agencies such as INEP. With this information in hand was our intention to answer some questions such as: Which schools contain computer lab with free software installed on the machines? How many teachers were trained in the use of free tools? Is there any pedagogical plan for the use of computers in the courses offered? That said, based on the answers, we built an online tool that would show anyone interested in Free Software and education, schools that use free software in their pedagogical practices, as well as the available equipment and installed software. In this way, greater access to information for possible exchange of experiences, new research, free software and education, or even teacher training for the use of tools will be possible.